2015
DOI: 10.1007/s13311-015-0387-1
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol as a Potential Treatment for Anxiety Disorders

Abstract: Cannabidiol (CBD), a Cannabis sativa constituent, is a pharmacologically broad-spectrum drug that in recent years has drawn increasing interest as a treatment for a range of neuropsychiatric disorders. The purpose of the current review is to determine CBD's potential as a treatment for anxiety-related disorders, by assessing evidence from preclinical, human experimental, clinical, and epidemiological studies. We found that existing preclinical evidence strongly supports CBD as a treatment for generalized anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
336
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(390 citation statements)
references
References 120 publications
11
336
2
15
Order By: Relevance
“…Studies have also shown that cannabis may have therapeutic use for anxiety,12 sleep disorders, appetite stimulation in the context of chemotherapy, fibromyalgia, post-traumatic stress disorder, and some aspects of the motor symptoms of Parkinson’s disease, as well as for the management of agitation in dementia, bladder dysfunction, glaucoma, and Tourette’s syndrome 6. Other indications are often cited anecdotally but so far lack a firm evidence base.…”
Section: Evidence Of Efficacymentioning
confidence: 99%
“…Studies have also shown that cannabis may have therapeutic use for anxiety,12 sleep disorders, appetite stimulation in the context of chemotherapy, fibromyalgia, post-traumatic stress disorder, and some aspects of the motor symptoms of Parkinson’s disease, as well as for the management of agitation in dementia, bladder dysfunction, glaucoma, and Tourette’s syndrome 6. Other indications are often cited anecdotally but so far lack a firm evidence base.…”
Section: Evidence Of Efficacymentioning
confidence: 99%
“…In addition, CBD may modulate emotional memory processing and decrease symptoms associated with emotional memory disorders such as post-traumatic stress disorder (PTSD; Blessing et al, 2015,Betthauser et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…One drug showing broad therapeutic potential in various psychiatric diseases is cannabidiol (CBD), the main non-psychotropic constituent of the Cannabis sativa plant (Izzo et al, 2009; see chemical structure of CBD in Figure 1A). Studies in humans demonstrate the promise of CBD for treating anxiety (Blessing et al, 2015) and preclinical studies in rodents are elucidating the pharmacological mechanisms underlying its acute anxiolytic effects. These mechanisms include potentiation of serotonin (5-HT) transmission via 5-HT 1A receptor (5-HT 1A R) activation and elevation of endocannabinoid levels via inhibition of their metabolism and re-uptake, which indirectly facilitates cannabinoid receptor type1 (CB1R) activation (for a review see Campos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%